Synthesis and Characterization of Co(II), Ni(II), Cu(II) and Cd(II) Complexes of Schiff Base Derived from 1,8-Diaminonaphthalene - Turan, N.; Sekerci, M. (Asian Journal of Chemistry, 2009)
A new Schiff base 8-amino-[1-(2-hydroxyphenyl)imino]naphthalene (LH) has been synthesized by the condensation of 1,8-diaminonaphthalene and salicylaldehyde. The complexes of the Schiff base were prepared with Co(II), Ni(II), Cu(II), Cd(II) chlorides in ethanol. The ligand and its metal complexes have been characterized by elemental analyses, magnetic susceptibility, molar conductance, IR, H-1, NMR and UV-Vis spectroscopy. The magnetic moment and electronic spectral data suggest tetrahedral structure for Ni(II) and Cd(II) complexes, square-planar geometry for Co(II) and Cu(II) complexes.
Keywords: 1,8-Diaminonaphthalene; Salicylaldehyde; Schiff base; Metal complexes